2019
DOI: 10.1002/jcb.28352
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA FLVCR1‐AS1 silencing inhibits lung cancer cell proliferation, migration, and invasion by inhibiting the activity of the Wnt/β‐catenin signaling pathway

Abstract: Long noncoding RNAs have been reported to be essential regulators in several human diseases, including tumorigenesis. A recent report revealed that FLVCR1-AS1 promotes the progression of hepatocellular carcinoma. However, whether FLVCR1-AS1 is involved in lung cancer remains unclear. In this study, we found that the expression of FLVCR1-AS1 was increased in lung cancer tissues according to The Cancer Genome Atlas database. Similarly, FLVCR1-AS1 was significantly upregulated in lung cancer cell lines. Knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
(88 reference statements)
2
22
0
Order By: Relevance
“…FLVCR1-AS1 expression has been reported to be upregulated in lung gastric and hepatocellular cancers [11][12][13][14]. Similarly, elevated FLVCR1-AS1 expressions were found in OSC tissues, serums, and cell lines in the current study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…FLVCR1-AS1 expression has been reported to be upregulated in lung gastric and hepatocellular cancers [11][12][13][14]. Similarly, elevated FLVCR1-AS1 expressions were found in OSC tissues, serums, and cell lines in the current study.…”
Section: Discussionsupporting
confidence: 72%
“…FLVCR1-AS1 is recently discovered upregulated in hepatocellular cancer, gastric cancer and lung cancer [11][12][13][14]. However, few studies have studied FLVCR1-AS1 in OSC.…”
mentioning
confidence: 99%
“…For example, Kumar et al (39) reported that mir-30b-3p acts as a direct regulator of androgen receptor signaling in prostate cancer. it was also reported that FlVcr1-aS1 may interact with mir-513, mir-573 and the Wnt/β-catenin signaling pathway in hepatocellular carcinoma, lung cancer and ovarian cancer (14)(15)(16)(17). Furthermore, liu et al (40) demonstrated that FlVcr1-aS1 can act as a sponge for mir-155, promoting therefore gastric cancer tumorigenesis by targeting c-Myc.…”
Section: Discussionmentioning
confidence: 96%
“…The lncrna Feline leukemia Virus Subgroup c cellular receptor 1 antisense rna 1 (FlVcr1-aS1) is a novel tumor suppressor located on chromosome 1q32.3 (13). Previous studies have identified impaired expression of FlVcr1-aS1 in hepatocellular carcinoma, lung cancer and ovarian cancer (14)(15)(16)(17); however, the underlying mechanism of FlVcr1-aS1 in glioma remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…41 The silence of FLVCR1-AS1 inhibits proliferation and migration of SPCA1 and A549 cells, resulting in Wnt/β-catenin signaling abrogation by notably downregulating target genes, such as CTNNB1, SOX4, cyclin D1, cyclin D2 (CCND2), and c-myc in SPCA1 and A549 cells. 42 GSK3β, which is regulated by the lncRNA MIR31HG, 43 the long intergenic non-protein coding RNA 968 (LINC00968; also known as LOC554202) 44 and lncRNA JPX, 45 is an important component of the Wnt/βcatenin signaling pathway. Studies have shown that the knockdown of MIR31HG represses Wnt/β-catenin signaling through down-regulating the expression of GSK3β and βcatenin, but increasing the phosphorylation of GSK3β in NSCLC cells.…”
Section: Cell Metastasis and Invasionmentioning
confidence: 99%